2006
DOI: 10.12723/mjs.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Diets on Survival and Growth of Striped Murrel Fry Channa Striatus

Abstract: Tubifix, Chiranomus, Beef liver, mosquito larvae and plankton used as feed were tested as diets in the early larval growth of Channa striatus fry over a 45 days period. Among all the food types Chironomus was found to produce the best growth results followed by tubifix, while other food types yielded poor results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…In the wild, Channa striata are wellknown as voracious predators; what little data are available in FishBase indicate a varied diet of benthic organisms and nekton, including fish, invertebrates (insects, worms, molluscs, crustaceans), and even frogs (Froese and Pauly, 2013). However, like Kumar et al (2008) we found that "little is known about their food preferences", in the wild or in captivity.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the wild, Channa striata are wellknown as voracious predators; what little data are available in FishBase indicate a varied diet of benthic organisms and nekton, including fish, invertebrates (insects, worms, molluscs, crustaceans), and even frogs (Froese and Pauly, 2013). However, like Kumar et al (2008) we found that "little is known about their food preferences", in the wild or in captivity.…”
Section: Introductionmentioning
confidence: 68%
“…All three feed treatments were high in protein (Table 1), and should be suitable for C. striata as a carnivorous fish, which can consume a wide variety of prey in the wild including invertebrates as well as fish (Kumar et al, 2008). This view is supported by the fact that all the fish remained in good condition throughout the study period, and it is reasonable to conclude that blue panchax, earthworms and golden apple snails can be acceptable to striped snakehead juveniles and could be used in the culture of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae of striped murrel need divergent food items of different sizes at different age/size. 39,[96][97][98][99][100] They are selective feeders and choice their prey depending on their mouth gape and preference for the prey size increases with the advancing of growth. 80 This shift in diet is probably required due to an increase in spacing between the gill rackers (the filtration apparatus on the gill arches) with advancing of age, where smaller food particles are filtered out and larger retained for ingestion by the larvae.…”
Section: Larval Feedsmentioning
confidence: 99%
“…A good number of studies on feeding striped murrel larvae using brine shrimp nauplii (BSN), decapsulated brine shrimp cyst, Cladocerans (Moina, Daphnia, Ceriodaphnia), copepods (Thermocyclops decipiens), tubificids (Tubifex spp), bloodworms (Chironomus spp), mosquito larvae and formulated feeds have been undertaken. [96][97][98]101,102 The results of these studies revealed that BSN is the best source of live feed to begin larval feeding in striped murrel and feeding with BSN could be continued up to 30 days if other live feed is unable to be sourced. The reason being the small size of BSN (length 0.251-0.348 mm and width 0.125-0.146 mm);…”
Section: Live Feedsmentioning
confidence: 99%
“…Dimana disini, terutama berhubungan dengan bentuk dan sistem pencernaan makanan dari benih ikan gabus tersebut yang belum terbiasa mengkonsumsi pakan buatan jenis (pellet) sehingga harus menyesuaikan diri mengingat ikan gabus adalah ikan jenis karnivora yang lebih menyukai pakan alami. Hal ini sesuai dengan pernyataan bahwa pembenihan ikan gabus yang baru menetas, post larva, fry merupakan proses yang rumit dan sangat kritis, (Kumar et al, 2008).…”
Section: Tingkat Kelangsungan Hidupunclassified